Comparing food consumption during the COVID-19 pandemic: analysis of household income and expenditure survey data in Iran - Mojtaba Hajipoor; Pegah Rahbarinejad; Kiyavash Irankhah; Seyyed Reza Sobhani (BMC, 2023)
Abstract Background On March 11, 2020, the WHO declared the outbreak of the infectious disease COVID-19 as a pandemic. The health strategies of nations lead to possible changes in lifestyle and increase poor eating habits. Hence, the purpose of this study is to compare food consumption during COVID-19 pandemic in Iran. Methods This cross-sectional study used secondary data from the Households Income and Expenditure Survey (HIES) conducted annually by the Statistical Centre of Iran. Food cost data of HIES included the amount of all food items in household food baskets during the last month. Then, they were classified into six food groups to evaluate their energy intake. The consequence of food consumption was analyzed as a function of socioeconomic status (SES) variables and residence pre- and post-COVID-19 pandemic. Results In total, 75,885 households (83.5% male) were included in the study. Among the population of urban and rural areas as well as in different SES categories, people tended to increase the consumption of meat (P < 0.05) and fresh foods, especially vegetable groups (P < 0.001) and decrease the consumption of fruit (P < 0.001), fat and sweets groups (P < 0.05) and also in energy intake (P < 0.05). Macronutrient changes were different in the category of SES, urban and rural. Conclusion Our study indicated that the COVID-19 pandemic had different effects on food groups, energy and macronutrients consumption, which could be due to possible changes in food patterns as a result of the pandemic.